Managing risk and patient involvement in choosing treatment for cancer: an analysis of two communication practices. Issue 8 (21st August 2017) - Alby, Francesca; Fatigante, Marilena; Zucchermaglio, Cristina
Abstract: Drawing on conversation analyses of oncology consultations collected in Italy, the article examines the communication practices used to recommend treatments. We found that the oncologist formulates the treatment recommendation (TR) for high‐risk patients in terms of a 'mandatory' choice and for low‐risk patients as an 'optional' type of decision. In the first case the doctor presses to reach a decision during the visit while in the second case leaves the decision open‐ended. Results show that high‐risk patients have less time to decide, are pressured towards choosing an option, but have more opportunities for involvement in TR during the visit. Low‐risk patients instead have more time and autonomy to make a choice, but they are also less involved in the decision‐making in the visit time. Moreover, we document that TR is organised through sequential activities in which the oncologist informs the patient of alternative therapeutic options while at the same time building a case for the kind of treatment she/he believes to be best for the patient's health. We suggest that in this field risk plays a key role in decision‐making which should be better understood with further studies and taken into account in the debate on shared decision‐making and patient‐centred communication.